Inherited IL-12p40 deficiency: genetic, immunologic, and clinical features of 49 patients from 30 kindreds. - Prando, C; Samarina, A; Bustamante, J; Boisson-Dupuis, S; Cobat, A; Picard, C; AlSum, Z; Al-Jumaah, S; Al-Hajjar, S; Frayha, H; Alangari, A; Al-Mousa, H; et al. (2013)
Autosomal recessive interleukin (IL)-12 p40 (IL-12p40) deficiency is a rare genetic etiology of mendelian susceptibility to mycobacterial disease (MSMD). We report the genetic, immunologic, and clinical features of 49 patients from 30 kindreds originating from 5 countries (India, Iran, Pakistan, Saudi Arabia, and Tunisia). There are only 9 different mutant alleles of the IL12B gene: 2 small insertions, 3 small deletions, 2 splice site mutations, and 1 large deletion, each causing a frameshift and leading to a premature stop codon, and 1 nonsense mutation. Four of these 9 variants are recurrent, affecting 25 of the 30 reported kindreds, due to founder effects in specific countries. All patients are homozygous and display complete IL-12p40 deficiency. As a result, the patients lack detectable IL-12p70 and IL-12p40 and have low levels of interferon gamma (IFN-γ). The clinical features are characterized by childhood onset of bacille Calmette-Guérin (attenuated Mycobacterium bovis strain) (BCG) and Salmonella infections, with recurrences of salmonellosis (36.4%) more common than recurrences of mycobacterial disease (25%). BCG vaccination led to BCG disease in 40 of the 41 patients vaccinated (97.5%). Multiple mycobacterial infections were rare, observed in only 3 patients, whereas the association of salmonellosis and mycobacteriosis was observed in 9 patients. A few other infections were diagnosed, including chronic mucocutaneous candidiasis (n = 3), nocardiosis (n = 2), and klebsiellosis (n = 1). IL-12p40 deficiency has a high but incomplete clinical penetrance, with 33.3% of genetically affected relatives of index cases showing no symptoms. However, the prognosis is poor, with mortality rates of up to 28.6%. Overall, the clinical phenotype of IL-12p40 deficiency closely resembles that of interleukin 12 receptor β1 (IL-12Rβ1) deficiency. In conclusion, IL-12p40 deficiency is more common than initially thought and should be considered worldwide in patients with MSMD and other intramacrophagic infectious diseases, salmonellosis in particular.